Sternbach Ludwik, Juridical Studies in Ancient Indian Law, Part II - Kunderewicz, Cezary (Czasopismo Prawno-Historyczne, 1969)
Recenzja: L. Sternbach, Juridical Studies in Ancient Indian Law, Part II„ ss. X+472, Motilal Banarsidass, Delhi—Varanasi—Patna, 1967. Rs. 50.